Commercially acquired açaí pulps contamination by Trypanosoma cruzi - Zapparoli, Diana [UNESP]; Bertozzo, Thainá Valente [UNESP]; Alexandrino, Marcela [UNESP]; Sanches, Daniela Filadelfo [UNESP]; Aires, Isabella Neves [UNESP]; Manzini, Suzane [UNESP]; de Medeiros, Maria Izabel Merino; Kurokawa, Cilmery Suemi [UNESP]; dos Santos, Rodrigo Mattos [UNESP]; Lucheis, Simone Baldini [UNESP] (Elsevier, 2022)
The etiological agent of Chagas disease is the protozoan Trypanosoma cruzi. According to the World Health Organization, about seven to eight million people are infected with T. cruzi worldwide. The main routes of transmission are vectorial and oral, which has assumed great epidemiological importance, since there is no legislation that requires the pasteurization of açaí pulp. The present work aimed to look T. cruzi in 35 samples of açaí ice cream sold at different points of sale, covering 11 different cities in São Paulo State. Thus, the parasitological technique of forced sieving and the molecular test of Polymerase Chain Reaction were performed. For PCR analysis were used the 121/122 primer that amplifies the kinetoplast of the T. cruzi DNA (kDNA). By the forced sieving technique, the açaí pulp aliquots were analyzed under different storage temperatures and in different periods. One positive sample (2.86%) were observed at six hours at room temperature, but without motility and negative to the PCR technique. Two other açaí samples (5.71%) were positive by PCR, but negative by forced sieving. The results indicate the need for quality control and good manufacturing practices for the safe consumption of açaí-derived products.
Keywords: Chagas disease; Diagnosis; Euterpe oleracea; Trypanosomiasis